Предмет: Алгебра,
автор: piano1234533
Люююдиии кто-нибудь помогите пожалуйста срочно!
Приложения:
Ответы
Автор ответа:
0
(㏒₁₁88- 1)*(1-㏒₈88)=(㏒₁₁(8*11) - 1)(1-㏒₈ (8*11)) =
=(㏒₁₁8+㏒₁₁11 - 1)(1- (㏒₈8+㏒₈11)) =(㏒₁₁8+1 - 1)(1-1-㏒₈11) =㏒₁₁8*(-㏒₈11)=
㏒8 ㏒11
= ----------- * (- ------- ) = -1
㏒11 ㏒8
=(㏒₁₁8+㏒₁₁11 - 1)(1- (㏒₈8+㏒₈11)) =(㏒₁₁8+1 - 1)(1-1-㏒₈11) =㏒₁₁8*(-㏒₈11)=
㏒8 ㏒11
= ----------- * (- ------- ) = -1
㏒11 ㏒8
Похожие вопросы
Предмет: Математика,
автор: Qweb0
Предмет: Математика,
автор: zasminakasym
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: дманавей